Merancang Kurikulum dengan Sentuhan Kemanusiaan: Perspektif Dimensi Manusia - Thuzahroh, Fatimah; Nurhayati (Jurnal Madako Education, 2021)
Curriculum planning is an essential aspect of creating an effective education system. From a human dimension perspective, curriculum planning not only focuses on learning materials but also needs to consider the characteristics, needs, and potential of the students. The background issue in this research is the mismatch between the existing curriculum and the evolving needs and interests of students, which are becoming increasingly diverse. The aim of this study is to analyze the importance of involving the human dimension in curriculum planning and making it a guideline in its development. The methodology used is library research, which reviews various theories of curriculum planning from the human dimension perspective. The findings indicate that the success of curriculum planning highly depends on the understanding of individual student needs, including their cognitive, social, and emotional aspects. Curriculum planning based on student characteristics is expected to result in more effective and relevant learning experiences, in line with the needs of the times. The conclusion of this study is that effective curriculum planning must comprehensively involve the human dimension to positively impact the intellectual, emotional, and social development of students in Indonesia.